Social Liability and the Unbroken Chains of Slavery in Mauritania - Gabbay, Shaul M. (Advances in Social Sciences Research Journal, 2025)
Although slavery has been legally abolished in Mauritania, it remains a deeply entrenched institution in practice. This paper argues that the persistence of slavery is not due to weak enforcement or bureaucratic inefficiencies, but rather to a deliberate system of preservation rooted in caste hierarchy, cultural conditioning, and state complicity. Drawing on survivors’ testimonies, expert reports, and sociological frameworks—including the concept of Social Liability—I explore how social networks that typically offer support as forms of Social Capital can instead operate as mechanisms of containment for enslaved populations. It also examines the government’s dual strategy of symbolic reform and quiet suppression, revealing how international donors and political allies often enable this facade. While centered on Mauritania, the paper situates the country within a broader global continuum of modern slavery, where marginalized communities are exploited for economic gain under the guise of legality and/or tradition. The findings call for a radical reimagining of abolition—one that prioritizes structural transformation, survivor leadership, and uncompromising honesty.